DAMPAK KONVERSI LAHAN SAWAH TERHADAP PRODUKSI PADI DI KABUPATEN BANTUL - Nursahera Juniati (FP AGRO 16 UMY 027, 2016)
This Research aimed to analyze the impact of the rice-field conversion on paddy production in Bantul Regency and to know the factors affecting the rice field conversion in Bantul Regency. The research was conducted in two subdistricts of Bantul regency (Banguntapan and Kasihan) from of December 2015 up to of April 2016. The research used survey method. The method consisted of data collecting, interview, and observation, the samples were taken by using purposive sampling technique, and all of the data were analyzed by simple linear regression to determine the influened of rice-field conversion to rice production.